2018
DOI: 10.1002/ijc.31522
|View full text |Cite
|
Sign up to set email alerts
|

Maternal residential pesticide use and risk of childhood leukemia in Costa Rica

Abstract: Evidence suggests that early‐life exposure to pesticides inside the home may be associated with childhood leukemia, however data from Latin American countries are limited. We examined whether self‐reported maternal residential pesticide use and nearby pesticide applications–before and after child's birth–were associated with acute lymphoblastic leukemia (ALL) in the Costa Rican Childhood Leukemia Study (CRCLS), a population‐based case‐control study (2001‐2003). Cases (n = 251 ALL) were diagnosed between 1995 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…(17,20,45) Consistent with these studies, a Costa Rican case-control study found an association between elevated childhood leukemia incidence and maternal insecticide use in the home and pesticide spraying on nearby farms before and after the child's birth. (46) An Italian case-control study showed an increase in leukemia risk among children residing close to arable crops. This study emphasized the need for further investigations into the role of passive exposure to herbicides and pyrethroids in disease occurrence in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…(17,20,45) Consistent with these studies, a Costa Rican case-control study found an association between elevated childhood leukemia incidence and maternal insecticide use in the home and pesticide spraying on nearby farms before and after the child's birth. (46) An Italian case-control study showed an increase in leukemia risk among children residing close to arable crops. This study emphasized the need for further investigations into the role of passive exposure to herbicides and pyrethroids in disease occurrence in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposure was also correlated with increased risk of prostate cancer in Canada (Band et al 2011). Furthermore, it was reported that in-utero environmental exposure to pesticides is associated with the development of childhood leukemia (Ferri et al 2018;Hyland et al 2018).…”
Section: Mutagenic and Carcinogenic Potentialmentioning
confidence: 99%
“…Non-genetic factors also contribute to ALL risk; for example, there is strong epidemiological evidence supporting a role for early life infections and modulation of the developing immune system in childhood ALL etiology, which has been reviewed in detail elsewhere [45] . Studies have also reported modest associations for childhood ALL risk with several environmental exposures [46] , including tobacco smoke [47][48][49] , pesticides [50,51] , paint [52,53] , and air pollution [54][55][56] . The vast majority of epidemiologic studies for ALL have been conducted in children, and very little is known regarding potential differences in ALL etiology across age groups.…”
Section: Introductionmentioning
confidence: 99%